Imaging Characteristics of Odontogenic Keratocysts: A Retrospective Radiographic Study - Admaja K. Nair; Fathimath Lamees; L. S. Sreela (Wolters Kluwer Medknow Publications, 2024)
Background: Odontogenic keratocyst (OKC) poses diagnostic challenges due to its aggressive nature and varied clinical as well as radiographic presentations, often resembling other cysts and tumors. The buccolingual to mesiodistal width ratio has been proposed as a potential radiographic parameter for diagnosing OKC. Aim: This study aimed to characterize OKC radiographically using cone beam computed tomography (CBCT) as well as panoramic radiographs, exploring the utility of the buccolingual to mesiodistal width ratio for diagnosis. Materials and Methods: An OKC retrospective radiography investigation was conducted with CBCT and panoramic radiographs from an archival database of patients in our institution, reported from 2019 to 2022. A total of 28 cases that were histopathologically confirmed OKC were analyzed. Results: Analyzing 28 histopathologically confirmed OKC cases, the mean age was 29.3 years, with a 3:4 female-to-male ratio. Predominantly located in the posterior mandible (60%), only one case occurred in the maxilla. The buccolingual to mesiodistal width ratio was <0.5 in 71% of cases, and over 80% exhibited unilocular radiolucency with scalloped borders. Conclusion: CBCT's width-length ratio has emerged as a significant diagnostic factor, though histopathology remains the gold standard. The research emphasizes the significance of considering radiographic parameters, with potential implications for OKC diagnosis.